2002
DOI: 10.1007/s00441-002-0529-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of the distribution of proliferating cells in the adult retina in three cyprinid species

Abstract: In the present study, a descriptive and quantitative analysis of all the proliferating cell populations present in the normal adult retina of three cyprinid species (goldfish, zebrafish, and tench) is reported. Evaluation of cell proliferation was performed in proliferating cell nuclear antigen (PCNA)-labeled tissue sections as well as in single-cell suspensions analyzed by flow cytometry. Our results show that the neural progenitors of the inner nuclear layer (INL) of cyprinids continue dividing in adulthood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 48 publications
1
14
0
3
Order By: Relevance
“…The differentiation process in the fish retina can be analyzed by monitoring the chronotopographical appearance of the layered retinal structure and functional synapses, the arrest of proliferative activity, or the appearance of a variety of neurochemical macromolecules selectively expressed by retinal cell types (Sandy and Blaxter, '80; Sharma and Ungar, '80; Vecino et al, '93; Kvenseth et al, '96; de Miguel Villegas et al, '97; Hagedorn et al, '98; Doldán et al, '99; Hu and Easter, '99; Helvik et al, 2001; Peterson et al, 2001; Mader and Cameron, 2004; Candal et al, 2005a, 2008; Arenzana et al, 2006; Kitambi and Malicki, 2008; Bejarano‐Escobar et al, 2009). Proliferating cell nuclear antigen (PCNA), an antigen expressed in the nuclei of cells during DNA replication, has previously been used to identify proliferating precursor cells in the teleost fish retina (Mack and Fernald, '97; Velasco et al, 2001; Cid et al, 2002; Candal et al, 2005a; Bernardos et al, 2007; Thummel et al, 2008; Bejarano‐Escobar et al, 2009). Thus, PCNA immunoreactivity has been observed in the juvenile and adult fish retina in different neurogenic niches, such as a neuroepithelial cell population located in the marginal edge of the retina that is called the circumferential germinal zone (CGZ), and proliferative cells located in the microenvironment around some Müller glia and in the outer nuclear layer (ONL) (Julian et al, '98; Otteson et al, 2001; Cid et al, 2002; Raymond et al, 2006; Bernardos et al, 2007; Thummel et al, 2008; Bejarano‐Escobar et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The differentiation process in the fish retina can be analyzed by monitoring the chronotopographical appearance of the layered retinal structure and functional synapses, the arrest of proliferative activity, or the appearance of a variety of neurochemical macromolecules selectively expressed by retinal cell types (Sandy and Blaxter, '80; Sharma and Ungar, '80; Vecino et al, '93; Kvenseth et al, '96; de Miguel Villegas et al, '97; Hagedorn et al, '98; Doldán et al, '99; Hu and Easter, '99; Helvik et al, 2001; Peterson et al, 2001; Mader and Cameron, 2004; Candal et al, 2005a, 2008; Arenzana et al, 2006; Kitambi and Malicki, 2008; Bejarano‐Escobar et al, 2009). Proliferating cell nuclear antigen (PCNA), an antigen expressed in the nuclei of cells during DNA replication, has previously been used to identify proliferating precursor cells in the teleost fish retina (Mack and Fernald, '97; Velasco et al, 2001; Cid et al, 2002; Candal et al, 2005a; Bernardos et al, 2007; Thummel et al, 2008; Bejarano‐Escobar et al, 2009). Thus, PCNA immunoreactivity has been observed in the juvenile and adult fish retina in different neurogenic niches, such as a neuroepithelial cell population located in the marginal edge of the retina that is called the circumferential germinal zone (CGZ), and proliferative cells located in the microenvironment around some Müller glia and in the outer nuclear layer (ONL) (Julian et al, '98; Otteson et al, 2001; Cid et al, 2002; Raymond et al, 2006; Bernardos et al, 2007; Thummel et al, 2008; Bejarano‐Escobar et al, 2009).…”
mentioning
confidence: 99%
“…Proliferating cell nuclear antigen (PCNA), an antigen expressed in the nuclei of cells during DNA replication, has previously been used to identify proliferating precursor cells in the teleost fish retina (Mack and Fernald, '97; Velasco et al, 2001; Cid et al, 2002; Candal et al, 2005a; Bernardos et al, 2007; Thummel et al, 2008; Bejarano‐Escobar et al, 2009). Thus, PCNA immunoreactivity has been observed in the juvenile and adult fish retina in different neurogenic niches, such as a neuroepithelial cell population located in the marginal edge of the retina that is called the circumferential germinal zone (CGZ), and proliferative cells located in the microenvironment around some Müller glia and in the outer nuclear layer (ONL) (Julian et al, '98; Otteson et al, 2001; Cid et al, 2002; Raymond et al, 2006; Bernardos et al, 2007; Thummel et al, 2008; Bejarano‐Escobar et al, 2009). Electron microscopy has commonly been used to verify the presence of morphological synapses in the plexiform layers during fish retinal development (Schmitt and Dowling, '99).…”
mentioning
confidence: 99%
“…This population of cells had been identified in larval fish (Hagedorn and Fernald, 1992;Johns, 1982). Subsequent to Julian et al's (1998) description, these proliferative events have been demonstrated in the retina of other adult teleosts (Cid et al, 2002;Otteson et al, 2001;Vihtelic and Hyde, 2000). This feature appears to exist in other salmonids (Ahlbert, 1976).…”
mentioning
confidence: 81%
“…We performed immunohistochemical detection of PCNA, an antigen expressed in the nuclei of cells during DNA replication, that has previously been used to identify proliferating precursor cells in the teleost fish retina (Mack and Fernald, 1997;Velasco et al, 2001;Cid et al, 2002;Candal et al, 2005;Bernardos et al, 2007;BejaranoEscobar et al, 2009;Bejarano-Escobar et al, 2010), and to investigate whether cell proliferation is affected by the incidence of constant high intensity light in experimental animals. Many PCNA-positive nuclei were found in the ciliary marginal zone (CMZ) in both control and experimental tench (Fig.8A,C,E).…”
Section: Proliferative Cells In the Experimental Larval Retinasmentioning
confidence: 99%